STATUS, TECHNOLOGIES AND STRATEGIES FOR INCREASING OILSEEDS PRODUCTION IN INDIA - S.N. SUDHAKARA BABU, VISHNU VARDHAN REDDY and (The Journal of Research, PJTSAU, 2017)
Vegetable oil shortage is a major concern for Indian economy to spend significant foreign exchange on import bill to meet more than 50% requirement of the country. The domestic oilseeds production is not meeting the pace of demand for vegetable oils driven by increased population with increased standard of living and growing industrial need. The demand for vegetable oil and oilseeds is increasing due to increase in population, increased standard of living and rapid industrialization. The per capita consumption of vegetable oils is rising continuously surpassing 18 kg/year during 2015-16. During the last two decades, edible oil consumption increased at a 4.3% compound annual growth rate and is expected to continue. The demand projections taking into account the trend of expenditure and price of food items suggest that the edible oil demand in the country to be 19.02 and 40.89 m t for 2025 and 2050. The future projection puts further concern with additional dimension of demand for biofuels. Despite the country is bestowed with wide agro-climatic situations for growing myriad oilseed crops, the productivity of annual oilseed crops in the country is low due to the sub-optimal agro-ecological growing conditions of majority rainfed cultivation (64%) and with inadequate and imbalanced nutrition especially of S, B and Zn, persistent biotic stresses and mostly grown by majority small and marginal farmers with low investment and management capacity. Besides, the production economics of oilseeds is discouraging in comparison with other competing crops.The strategies for research, development and policy for increasing oilseeds production in short and long term basis have been crafted for priority persuasion. With the desired policy support of ensured MSP, liberalsupport for expanding irrigation facility, small holding mechanization and oil content based premium pricing would provide fillip for higher technology adoption.